Analisa dan Rancangan Sistem Informasi Pariwisata Pacitan dengan UML dan ERD - Berlian Juliartha Martin Putra; Anwar Fu’adi; Dwi Ariani Finda Yuniarti (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2022)
Pacitan Kota Seribu Goa dimana pacitan memiliki banyak goa, pantai dan tempat wisata sehingga pacitan terkenal akan keindahan pariwisatanya. Saat ini, Pacitan belum memiliki sistem yang mengelola informasi-informasi pariwisata di Pacitan sehingga pengunjung akan mengumpulkan informasi-informasi yang terdapat di blog – blog satu persatu selain itu banyak tempat wisata pacitan yang belum diketahui pengunjung yang sebenarnya dapat dijadikan alternatif kunjungan wisata sehingga diperlukan sistem informasi pariwisata pacitan. Sistem Informasi yang akan dibangun terlebih dahulu harus dilakukan analisa dan rancangan. Tujuan penelitian ini melakukan analisa dan rancangan sistem informasi pariwisata Pacitan. Penelitian dimulai dari mengumpulkan sumber referensi, mengumpulkan data, analisa dan merancang sistem. Penelitian ini menghasilkan analisa sistem informasi pariwisata pacitan berupa Use Case Diagram dan Activity Diagram serta rancangan sistem informasi(SI) pariwisata pacitan berupa Entity Relationship Diagram, Class Diagram dan rancangan untuk antar muka pengguna. Analisa dan Rancangan Sistem Informasi Pariwisata ini berguna ketika implementasi ke sistem informasi pariwisata pacitan. Abstract: Pacitan City of a Thousand Caves where Pacitan has many caves, beaches and tourist attractions so that Pacitan is famous for the beauty of its tourism. Currently, Pacitan does not yet have a system that manages tourism information in Pacitan so that visitors will collect information contained in blogs one by one besides that there are many Pacitan tourist attractions that are not yet known to visitors which can actually be used as an alternative to tourist visits so a system is needed. Pacitan tourism information, while in the early stages of building an information system, analysis and design must first be carried out. This study aims to analyze and design a tourism information system in Pacitan. Research starts from collecting reference sources, collecting data, analyzing and designing systems. The research uses the waterfall method, where in this study there are still three initial stages in the method, namely collecting user needs, analyzing and designing information systems. This study resulted in an analysis of the Pacitan tourism information system in the form of Use Case Diagrams and Activity Diagrams and the design of the Pacitan tourism information system (SI) in the form of Entity Relationship Diagrams, Class Diagrams and designs for user interfaces. Analysis and Design of this Tourism Information System can be used to be implemented into tourism information systems, especially tourism in Pacitan Regency.